Role of Myeloid-Epithelial-Reproductive Tyrosine Kinase and Macrophage Polarization in the Progression of Atherosclerotic Lesions Associated With Nonalcoholic Fatty Liver Disease - Pastore, Mirella; Grimaudo, Stefania; Pipitone, Rosaria Maria; Lori, Giulia; Raggi, Chiara; Petta, Salvatore; Marra, Fabio (Frontiers in Pharmacology, 2019)
Recent lines of evidence highlight the involvement of myeloid-epithelial-reproductive tyrosine kinase (MerTK) in metabolic disease associated with liver damage. MerTK is mainly expressed in anti-inflammatory M2 macrophages where it mediates transcriptional changes including suppression of proinflammatory cytokines and enhancement of inflammatory repressors. MerTK is regulated by metabolic pathways through nuclear sensors including LXRs, PPARs, and RXRs, in response to apoptotic bodies or to other sources of cholesterol. Nonalcoholic fatty liver disease (NAFLD) is one of the most serious public health problems worldwide. It is a clinicopathological syndrome closely related to obesity, insulin resistance, and oxidative stress. It includes a spectrum of conditions ranging from simple steatosis, characterized by hepatic fat accumulation with or without inflammation, to nonalcoholic steatohepatitis (NASH), defined by hepatic fat deposition with hepatocellular damage, inflammation, and accumulating fibrosis. Several studies support an association between NAFLD and the incidence of cardiovascular diseases including atherosclerosis, a major cause of death worldwide. This pathological condition consists in a chronic and progressive inflammatory process in the intimal layer of large- and medium-sized arteries. The complications of advanced atherosclerosis include chronic or acute ischemic damage in the tissue perfused by the affected artery, leading to cellular death. By identifying specific targets influencing lipid metabolism and cardiovascular-related diseases, the present review highlights the role of MerTK in NAFLD-associated atherosclerotic lesions as a potential innovative therapeutic target. Therapeutic advantages might derive from the use of compounds selective for nuclear receptors targeting PPARs rather than LXRs regulating macrophage lipid metabolism and macrophage mediated inflammation, by favoring the expression of MerTK, which mediates an immunoregulatory action with a reduction in inflammation and in atherosclerosis.